Arbovirus surveillance in emergency care units in Salvador, Brazil - Ms Fernanda Lopes Habib; Ms Adryele Figueiredo Pinheiro; Mr Marcos Silva Brito; Ms Natalie Nascimento Oliveira; Mr Davi Lemos Bastos; Dr Bernardo Gratival Gouvea Costa; Dr Gessica Almeida Vasconcelos; Ms Marta Giovanetti; Dr Isadora de Siqueira (International Journal of Infectious Diseases)
Introduction: Dengue, Zika, and Chikungunya are endemic arboviruses in Brazil, presenting significant healthcare challenges due to their similar symptoms and the difficulties in laboratory diagnosis, which lead to an underestimation of the true number of infections. This study aims to elucidate the emergence and reemergence of these arboviruses in new regions. Methods: A cross-sectional study was conducted at two emergency care units in Salvador, Brazil, from April 2023 to March 2024. Patients with fever in the last seven days and associated symptoms such as skin rash, retroocular pain, myalgia, and arthralgia were included. Respiratory symptoms were exclusion criteria. Data were collected using REDCap (v.9.3.1 © 2023), and blood samples were taken. RNA extraction was performed using the QIAamp MinElute Virus Spin Kit (QIAGEN), and RT-qPCR was conducted with the ZDC kit (IBMP). Serological analysis was carried out using Euroimmun (Lübeck, Germany) kits to detect Dengue and Chikungunya antibodies. Results: A total of 351 participants were enrolled, with 327 providing samples. The majority were women (218; 62.1%) of mixed race (156; 44.8%), with a median age of 29 years. RT-qPCR identified 25 samples positive for DENV1, two for DENV2, and eight for Chikungunya. Other serotypes were not detected. Serological analysis showed 64 (25.9%) samples positive for NS1 Dengue antigen, and 124 (68.9%) positive for Dengue IgM. For Chikungunya, six (6.6%) samples were positive for IgM, and one (1%) was positive for Zika IgM. IgG seroprevalence was 70.1% for Dengue (n = 124), 27.6% for Chikungunya (n = 58), and 56.6% for Zika (n = 164). Discussion: Positive qPCR samples were forwarded for sequencing. A metagenomic approach will be applied to samples that were negative in all tests (PCR, IgM, and NS1). Conclusion: The study identified a high prevalence of arboviruses, underscoring their extensive circulation in the region. Genomic analysis of the viruses is essential to better understand their dynamics and introduction in the area.